Local currency model: to boost economic activities of indigenous community in Malaysia - Duasa, Jarita; Mohd Thas Thaker, Mohamed Asmy; Rahman, Maya Puspa (2018)
The study proposes the local currency model to the Malaysian Indigenous community (Orang Asli) since they are among the nation's hardcore poor. It attempts to measure the probability and level of acceptance in the community if the complementary currency system were to be introduced for their economic activities. Using primary data collected from the survey among Orang Asli in Peninsular Malaysia, the study analyzes the data using Logit model and Technology Acceptance Model (TAM). Results from logistic regression imply that the probability to opt for proposed local currency as an alternative currency is high if it is using agricultural products and backed by national currency. The probability is also high among higher income respondents but low for those with big family size and those who prefer to use Ringgit Malaysia (RM). Using TAM, it is found that ‘perceived usefulness’ and ‘perceived ease of use’ have positive effect on ‘attitude’ to use the proposed local currency. Similar results are found between ‘perceived usefulness’ and ‘behavioral intention’ to use the proposed currency. Thus, through positive attitude, the respondent’s perceptions on the usefulness and ease of use positively affect the behavioral intention of using the new system. The findings could assist the policymakers in implementing local currency model to Orang Asli community to boost their economic activities and pull them out from the circle of hardcore poverty among nations.